2014
DOI: 10.2215/cjn.05870513
|View full text |Cite
|
Sign up to set email alerts
|

Should an Elderly Patient with Stage V CKD and Dementia Be Started on Dialysis?

Abstract: The burden of cognitive impairment appears to increase with progressive renal disease, such that the prevalence of dementia among those starting dialysis, or those already established on dialysis, is high. The appropriateness of dialysis initiation in this population has been questioned, and current Renal Physician Association guidelines suggest forgoing dialysis in individuals who have dementia and lack awareness of self and environment. Patients are, however, also entitled to equal rights and respect, equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our data may support the recommendation of the Renal Physician Association (RPA), which suggest that patients with advanced dementia be advised against initiation of dialysis, particularly when they are unable to cooperate with the dialysis process. [10,32] Supporting this recommendation, the Dialysis Advisory Group of the American Society of Nephrology suggested that dialysis patients with life expectancy of <1 year may desire a palliative approach to dialysis care, which focuses on aligning patient treatment with patients’ informed preferences. [9] The RPA emphasizes the need for establishing a strong therapeutic relationship and open communication to facilitate shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Our data may support the recommendation of the Renal Physician Association (RPA), which suggest that patients with advanced dementia be advised against initiation of dialysis, particularly when they are unable to cooperate with the dialysis process. [10,32] Supporting this recommendation, the Dialysis Advisory Group of the American Society of Nephrology suggested that dialysis patients with life expectancy of <1 year may desire a palliative approach to dialysis care, which focuses on aligning patient treatment with patients’ informed preferences. [9] The RPA emphasizes the need for establishing a strong therapeutic relationship and open communication to facilitate shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…These patients generally have difficulty to express their treatment-related symptoms. In addition, they are less likely to understand or to tolerate the dialysis process [8, 10, 1921]. Several studies, including a recent nationwide population-based study in Taiwan, revealed that dementia is strongly and independently associated with morbidity and mortality not only in the general elderly population but also in ESRD patients [8, 10, 22–24].…”
Section: Introductionmentioning
confidence: 99%
“…Dialysis requires patients to sit still for 4–5 hours and tolerate the sometimes traumatic insertion of fistula needles or other problems with vascular access. Patients who are confused or distressed might disconnect lines, disrupt equipment and put other patients at risk, requiring the use of physical or chemical restraint . The RPA/ASN guidelines emphasize that the ability to cooperate with dialysis is a prerequisite as restraint use constitutes undue treatment burden and an infringement of human rights.…”
Section: Dialysis Burden Of Care—issues For Patients With Dementiamentioning
confidence: 99%